Analysis Of Pollution Haven Hypothesis In World Trade Organization Member Countries - Gita Ayu Kusuma; Ni Putu Wiwin Setyari (Jurnal Ekonomi Kuantitatif Terapan, 2024)
The threat of climate change, justice and also inequality are subjective proxies in the SustainableDevelopment Goals (SDGs). Likewise with free trade carried out by every country in the world to meet the needsof society. Free trade began to appear when the rounds at the World Trade Organization (WTO) in Dohaaimed toremove trade distortions in the international trade regime, so as to encourage an increase in world trade. Therace of countries in the world to pursuewealth and prosperity has several impacts on the environment, one ofwhich is global warming caused by greenhouse gases. The main greenhouse gas thatcontinues to increase iscarbon dioxide. The purpose of this study is to analyze the Pollution Haven Hypothesis (PHH) model in explainingthe relationship between foreign investment, trade openness, income per capita, renewable energy consumption,non-renewable energy consumption and urban population on the environmental quality of WTO membercountries. This research is an associative quantitative research conductedon WTO members with a sample size of108 countries. Data collection was obtainedthrough the World Bank Index which was then analyzed using theAutoregressive Distributed Lag (ARDL) method. The results of the study showthat the Pollution Haven Hypothesismodel notoccurs in WTO member. However, in the long run the investment has a reduced emission impact on thehost country. This is proof of the existence of the Halo Pollution Hypothesis.